Peran Kompetensi Sosial Guru dalam Mewujudkan Hubungan Harmonis di Lingkungan Pendidikan - Aisha Barokah; Nadila Amri; Windri Gusnita; Ade Irma (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
This study aims to examine the implementation of social competence of teachers in three secondary schools with different characteristics, namely SMAN 1 Tambang, Al-Ihsan Boarding School and SMAN 12 Pekanbaru. Social competence does not only include the ability to communicate, but also interact and build positive relationships with students, fellow teachers, parents, and the surrounding community, which are very important in planning and implementing effective and enjoyable classroom learning. Using a qualitative approach, data were collected through semi-structured interviews and direct observations to explore the experiences of teachers, principals, and students in the daily learning process. The results of the study showed variations in the application of social competence which were influenced by social environmental factors, facilities, and teacher readiness in responding to changes in education policy. Despite facing challenges such as limited facilities and administrative burdens, some teachers were able to demonstrate high dedication and innovation in learning. This study provides a comprehensive picture of social practices in the field and is expected to be an input in formulating policies to improve teacher quality contextually and sustainably.